Big Data Analytics: Techniques, Tools, and Applications in Various Industries - Ramadhan, Gildan Jaya Muhammad; Niam, Sukron (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2023)
Big data analytics has emerged as a powerful tool for extracting valuable insights from large and complex datasets across diverse industries. This article provides a comprehensive review of the techniques, tools, and applications of big data analytics in various industries. Through qualitative analysis and extensive literature review, this study explores the key methods and technologies used in processing and analyzing massive volumes of data to uncover hidden patterns, trends, and correlations. The article discusses the significance of big data analytics in enhancing decision-making processes, optimizing operations, and gaining competitive advantages in today's data-driven economy. Furthermore, it examines the challenges and opportunities associated with implementing big data analytics solutions across different sectors. By examining real-world case studies and industry examples, this research highlights the practical applications of big data analytics in areas such as healthcare, finance, manufacturing, retail, and marketing. The findings underscore the transformative impact of big data analytics on improving business performance, customer engagement, and innovation across diverse domains. Overall, this article aims to contribute to the understanding of big data analytics techniques and their wide-ranging applications, providing insights for researchers, practitioners, and decision-makers in leveraging data-driven approaches to drive organizational success.